All Aspects of Pedophilia - Polat, Oğuz (The Bulletin of Legal Medicine, 2015)
Pedophilia is a deviant sexual behavior which is a sub-category of paraphilias. If acted out, pedophilia is legally defined as sexual child abuse. Pedophilia includes fondling a child’s genitals, intercourse, rape, sodomy, exhibitionism, and commercial exploitation of children through prostitution or the production of pornographic materials. Pedophiles who have sexually abused children require intense psychological and pharmacological therapy prior to release into the community because of the high rate of repeat offenders. The incidence of pedophilia has been markedly underestimated. It is often discussed whether sexual offenders of children are pedophiles or child molesters. It depends on exact definition and operationalizational categorization .Practical question from forensic point of view is whether there are any differences between the group of ’pedophiles’, who have sexually offended child and the group of child molesters, who do not meet criteria for pedophilia. It confirms the opinion that not all of child sexual offenders are pedophiles. Regarding pedophilia remains the problem of its definition in conditions of practical acceptance. Keywords: Pedophilia, Child sexual abuse, paraphilia